Anemia and Fatigue in Patients with Chronic Kidney Failure - Maisyaroh, Arista; Maslufin, M; Fibriyanti, Dwi Ochta; Widianto, Eko Prasetya; Kurnianto, Syaifuddin (Jurnal Kesehatan Manarang, 2024)
Chronic renal failure results in impaired kidney function, effectively eliminating metabolic waste and regulating fluid and electrolyte balance. The accumulation of waste metabolites is thought to impact the occurrence of anemia and fatigue. However, no research has shown a correlation between the incidence of anemia and fatigue in sufferers of chronic kidney failure. This study aimed to evaluate the relationship between hemoglobin levels and the degree of fatigue experienced by individuals diagnosed with chronic kidney disease. This research uses a cross-sectional study approach. The study population consisted of patients with chronic kidney failure at one of the hospitals in Lumajang Regency who were identified by the indicator of high BUN values. The sample size for this research was 50 people selected through purposive sampling. The data type used is primary data, with the independent variable being the Hb value, while the dependent variable is the level of fatigue in chronic kidney failure patients. The results of the Pearson correlation test in this study showed that there was a significant relationship between the percentage of hemoglobin levels in the blood and the level of fatigue in chronic kidney failure patients (p-value = <0,000; Î± = 0.05), with a strength of relationship 0,6092 which means the level Hemoglobin in the blood and the level of fatigue have a perfect degree of correlation. In patients with chronic renal failure and low hemoglobin levels, their fatigue levels will become more severe. Insufficient hemoglobin levels lead to a reduced count of red blood cells, causing a decline in the body's capacity to transport oxygen. This inadequate oxygen supply hampers the oxidation process and energy production in the form of ATP within the body's cells. Consequently, patients with chronic renal failure may undergo a substantial decrease in energy levels and experience significant tiredness.